Beneficial effects of silicon on photosynthesis of tomato seedlings under water stress - Yi ZHANG; Yu SHI; Hai-jun GONG; Hai-liang ZHAO; Huan-li LI; Yan-hong HU; Yi-chao WANG (Journal of Integrative Agriculture)
Silicon can improve drought tolerance of plants, but the mechanism still remains unclear. Previous studies have mainly concentrated on silicon-accumulating plants, whereas less work has been conducted in silicon-excluding plants, such as tomato (Solanum lycopersicum L.). In this study, we investigated the effects of exogenous silicon (2.5 mmol L−1) on the chlorophyll fluorescence and expression of photosynthesis-related genes in tomato seedlings (Zhongza 9) under water stress induced by 10% (w/v) polyethylene glycol (PEG-6000). The results showed that under water stress, the growth of shoot and root was inhibited, and the chlorophyll and carotenoid concentrations were decreased, while silicon addition improved the plant growth and increased the concentrations of chlorophyll and carotenoid. Under water sterss, chlorophyll fluorescence parameters such as PSII maximum photochemical efficiency (Fv/Fm), effective quantum efficiency, actual photochemical quantum efficiency (ϕPSII), photosynthetic electron transport rate (ETR), and photochemical quenching coefficient (qP) were decreased; while these changes were reversed in the presence of added silicon. The expressions of some photosynthesis-related genes including PetE, PetF, PsbP, PsbQ, PsbW, and Psb28 were down-regulated under water stress, and exogenous Si could partially up-regulate their expressions. These results suggest that silicon plays a role in the alleviation of water stress by modulating some photosynthesis-related genes and regulating the photochemical process, and thus promoting photosynthesis.